Radio wave absorber, radio wave absorbing structure comprising same, and composition for radio wave absorber
By unevenly distributing carbon fibers in the resin matrix and adding hollow particles and carbon particles, the resin structure is optimized, and the problems of the thickness and weight of the existing millimeter-wave radar radio wave absorber are solved, and thinner and efficient radio wave absorption performance is achieved, suitable for 75GHz~105GHz frequency band.
Patent Information
- Application Number
- CN202380039752.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-12
- Filing Date
- 2023-04-25
- Publication Date
- 2024-12-20
AI Technical Summary
The existing millimeter-wave radar's radio wave absorber has difficulty achieving the goal of thinner and lighter when maintaining the thickness and weight requirements of high radio wave absorption characteristics, which affects the miniaturization and lightweighting of the device.
By making carbon fibers unevenly present in the resin matrix, 60 to 90% of the volume of the carbon fibers are concentrated in half of the thickness, and hollow particles and carbon particles are added to the radio wave absorber, the organosiloxane structure of the resin is optimized to improve the Radio wave absorption performance.
It realizes a radio wave absorber that is thinner than the traditional method and has high radio wave absorption characteristics, which is suitable for the frequency band of 75GHz to 105GHz, meeting the demand for miniaturization and lightweight of millimeter-wave radar devices.
Smart Images

Figure CN119174297A_ABST
Abstract
Description
Technical Field
[0001] The technology disclosed herein relates to a radio wave absorber, a radio wave absorbing structure including the radio wave absorber, and a composition for a radio wave absorber. Background Art
[0002] In modern society, radio waves are used in various fields such as broadcasting, communication, medical treatment, chemical analysis, location determination, remote operation, etc. For example, millimeter wave radar using radio waves in the frequency band of 30 to 300 GHz is one of the important technologies supporting vehicle autonomous driving.
[0003] Millimeter wave radar uses radio waves in the above frequency bands to measure the distance, speed, and angle to the target. Taking vehicle autonomous driving as an example, as one of the technologies used, with the popularization of ADAS (Advanced Driving Assistance System), 76-77GHz millimeter wave radars that can detect long distances are used as forward monitoring radars. Millimeter wave radars emit millimeter waves, and by receiving millimeter waves reflected by the target with a receiving antenna, they detect the distance to the target, etc.
[0004] In a millimeter wave radar device, a shielding member for shielding radio waves is provided between an antenna and a control circuit, thereby suppressing a decrease in detection accuracy caused by reception of millimeter waves reflected by objects other than a target (such as a road surface).
[0005] As shield members, for example, Patent Documents 1 and 2 disclose molded bodies and compositions containing resin and carbon fibers.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2019-161208
[0009] Patent Document 2: Japanese Patent Application Publication No. 2020-111730 Summary of the invention
[0010] Since sensors such as millimeter wave radars are required to be smaller and lighter, radio wave absorbers (shielding members) as constituent members are also required to be thinner and lighter while maintaining high radio wave absorption characteristics.
[0011] The object of the technology disclosed in the present invention is to provide a radio wave absorber having high radio wave absorption characteristics and being thinner than before. Another object is to provide a radio wave absorption structure and a composition for a radio wave absorber including the radio wave absorber.
[0012] The inventors of the present invention conducted intensive research and found that by making the carbon fibers unevenly distributed (biased) on one side in the thickness direction of the resin serving as the matrix, a thin radio wave absorber having high radio wave absorption properties can be obtained even if the amount of carbon fibers added is reduced, thereby completing the technology disclosed in the present invention.
[0013] According to the technology disclosed in the present invention, the following radio wave absorber and the like are provided.
[0014] 1. A radio wave absorber comprising a resin and carbon fibers,
[0015] 60 to 90 volume % of the entire carbon fibers are present in a region from the first surface to half of the total thickness.
[0016] 2. The radio wave absorber according to 1, wherein the content of the carbon fibers is 2% by volume or less of the total volume.
[0017] 3. The radio wave absorber according to 1 or 2, further comprising hollow particles in an amount of 10 volume % or less of the total volume.
[0018] 4. The radio wave absorber according to any one of 1 to 3, wherein the average length of the carbon fibers is 100 to 4000 μm.
[0019] 5. The radio wave absorber according to any one of 1 to 4, wherein the resin has an organosiloxane structure represented by the following formula (1):
[0020] [Chemistry 1]
[0021]
[0022] (Where R 1 and R 2 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms).
[0023] 6. The radio wave absorber according to any one of 1 to 5, further comprising carbon particles in an amount of 10% by volume or less of the total volume.
[0024] 7. The radio wave absorber according to any one of 1 to 6, wherein the amount of radio wave absorption in the entire frequency range of 75 GHz to 105 GHz is 30% or more.
[0025] 8. A radio wave absorbing structure comprising the radio wave absorber according to any one of 1 to 7, and a radio wave reflector, wherein the radio wave reflector is laminated on the side of the radio wave absorber on which the carbon fibers are unevenly present.
[0026] The thickness of the radio wave absorber is 200 to 500 μm.
[0027] 9. The radio wave absorption structure according to 8, wherein the amount of radio wave absorption in the entire frequency range of 75 GHz to 105 GHz is 30% or more.
[0028] 10. A composition for a radio wave absorber, comprising a resin having an organosiloxane structure represented by the following formula (1), carbon fibers, hollow particles, and carbon particles,
[0029] The carbon fiber content in the solid component is less than 2 volume %,
[0030] The content of the hollow particles in the solid component is less than 10% by volume,
[0031] The content of the carbon particles in the solid component is less than 10% by volume,
[0032] [Chemistry 2]
[0033]
[0034] (Where R 1 and R 2 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms).
[0035] According to the technology disclosed in the present invention, a thin radio wave absorber having high radio wave absorption characteristics can be provided. In addition, a radio wave absorption structure and a composition for a radio wave absorber including the radio wave absorber can be provided.
[0036] Brief description of the attached figure
[0037] Figure 1 This is a schematic cross-sectional view of a radio wave absorber according to one embodiment of the disclosed technology.
[0038] Figure 2 This is a schematic cross-sectional view of a radio wave absorption structure according to one embodiment of the disclosed technology.
[0039] Figure 3 This is a graph showing the difference in complex dielectric constant between the radio wave absorbers produced in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0040] [Radio wave absorber]
[0041] A radio wave absorber according to one embodiment of the disclosed technology includes a resin and carbon fibers, wherein 60 to 90 volume % of all the carbon fibers are present in a region from the first surface to half of the total thickness.
[0042] Figure 1 This is a schematic cross-sectional view of a radio wave absorber according to an embodiment of the disclosed technology. The radio wave absorber 1 is a sheet of thickness T containing resin and carbon fibers. The distance between the first surface 11 and the second surface 12, i.e., the thickness is T. In this embodiment, 60 to 90% by volume of all carbon fibers are present in the region A from the first surface 11 to half of the total thickness T (thickness t = 0.5T). That is, the carbon fibers are unevenly present in the region A on the first surface 11 side compared to the region B on the second surface 12 side. It should be noted that in the horizontal direction (the direction of the surface irradiated with radio waves), the carbon fibers are evenly dispersed without any deviation in density.
[0043] By making the carbon fibers non-uniformly present on the first surface 11 side, the radio wave absorption can be improved compared to a case where an equal amount of carbon fibers are uniformly dispersed.
[0044] If the ratio of carbon fibers in region A of the radio wave absorber 1 is low, a network between the carbon fibers cannot be formed well, and the dielectric constant of the radio wave absorber 1 decreases. If the carbon fibers settle and are too unevenly distributed in region A, the radio wave absorber 1 deviates from an appropriate dielectric constant.
[0045] The proportion (volume %) of the carbon fibers present in region A is determined by measuring the sample using a microfocus X-ray CT device, reconstructing a 3D image using image analysis software, and extracting the carbon fibers three-dimensionally based on the contrast of the image data caused by the difference in the X-ray absorption coefficients of the resin and the carbon fibers. Details are described in the Examples.
[0046] The ratio of the carbon fibers present in the region A is preferably 65 to 90% by volume, particularly preferably 66 to 90% by volume.
[0047] Hereinafter, constituent members and the like of the radio wave absorber will be described.
[0048] <Resin>
[0049] Examples of the resin used in the present embodiment include silicone resins, epoxy resins, phenolic resins, polyurethane resins, thermosetting polyimides, unsaturated polyester resins, alkyd resins, etc. These resins may be used alone or in combination of two or more.
[0050] It is preferable to use an appropriate curing agent according to the type of resin.
[0051] In one embodiment, from the viewpoint of easy adjustment of the dielectric constant of the radio wave absorber, a resin having an organic siloxane structure is preferred. Examples of the organic siloxane structure include a structure represented by the following formula (1).
[0052] [Chemistry 3]
[0053]
[0054] (Where R 1 and R 2 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms).
[0055] In formula (1), as R 1 and R 2 The halogen atom independently represented by each of them includes a fluorine atom, a chlorine atom, a bromine atom and an iodine atom. 1 and R 2 The alkyl group independently represented by each group includes methyl, ethyl, n-propyl, isopropyl, various butyl groups ("various" means groups including straight-chain and all branched groups, the same applies below), various pentyl groups and various hexyl groups. 1 and R 2 The alkoxy group independently represented by each of them includes the case where the alkyl moiety is the above-mentioned alkyl group. 1 and R 2 Examples of the aryl group independently represented include phenyl and naphthyl.
[0056] As R 1 and R 2 , preferably all are hydrogen atoms, alkyl groups having 1 to 6 carbon atoms, alkoxy groups having 1 to 6 carbon atoms, or aryl groups having 6 to 12 carbon atoms, and more preferably all are methyl groups.
[0057] Examples of the resin having an organosiloxane structure include polyorganosiloxanes such as polydimethylsiloxane.
[0058] In one embodiment, the resin having an organosiloxane structure is preferably a copolymer having the structure represented by the above formula (1) and another structure. By using a copolymer, viscosity adjustment may be easier during production of the radio wave absorber.
[0059] Examples of copolymers having the structure represented by the above formula (1) and other structures include polycarbonate-polyorganosiloxane copolymers.
[0060] Examples of the polycarbonate structure of the copolymer include a structure represented by the following formula (2).
[0061] [Chemistry 4]
[0062]
[0063] (Where R 3 and R 4Each independently represents a halogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms. X represents a single bond, an alkylene group having 1 to 8 carbon atoms, an alkylidene group having 2 to 8 carbon atoms, a cycloalkylene group having 5 to 15 carbon atoms, an arylene group having 6 to 12 carbon atoms, a cycloalkylidene group having 5 to 15 carbon atoms, a fluorenediyl group, an arylalkylene group having 7 to 15 carbon atoms, an arylalkylidene group having 7 to 15 carbon atoms, -S, -SO-, -SO2-, -O-, or -CO-).
[0064] In formula (2), as R 3 and R 4 Examples of the halogen atom independently represented include a fluorine atom, a chlorine atom, a bromine atom and an iodine atom.
[0065] As R 3 and R 4 The alkyl group independently represented by each of them includes methyl, ethyl, n-propyl, isopropyl, various butyl groups, various pentyl groups and various hexyl groups. 3 and R 4 The alkoxy groups independently represented include those in which the alkyl moiety is the above-mentioned alkyl group.
[0066] Examples of the alkylene group represented by X include methylene, ethylene, trimethylene, tetramethylene, hexamethylene, etc., and preferably an alkylene group having 1 to 5 carbon atoms. Examples of the alkylidene group represented by X include ethylidene, isopropylidene, etc. Examples of the cycloalkylene group represented by X include cyclopentanediyl, cyclohexanediyl, cyclooctanediyl, etc., and preferably a cycloalkylene group having 5 to 10 carbon atoms. Examples of the arylene group represented by X include phenylene, naphthylene, biphenylene, etc. Examples of the cycloalkylidene group represented by X include cyclohexylidene, 3,5,5-trimethylcyclohexylidene, 2-adamantylene, etc., and preferably a cycloalkylidene group having 5 to 10 carbon atoms, and more preferably a cycloalkylidene group having 5 to 8 carbon atoms. Examples of the aryl moiety of the arylalkylene group represented by X include aryl groups having 6 to 14 ring carbon atoms such as phenyl, naphthyl, biphenyl, anthracenyl, etc. Examples of the aryl moiety of the arylalkylidene group represented by X include aryl groups having 6 to 14 ring carbon atoms, such as phenyl, naphthyl, biphenylyl and anthracenyl.
[0067] a and b each independently represent an integer of 0 to 4, preferably 0 to 2, more preferably 0 or 1. Among them, a and b are 0, X is a single bond or an alkylene group having 1 to 8 carbon atoms, or a and b are 0, X is an alkylidene group, especially an isopropylidene group.
[0068] For details of polycarbonate-polyorganosiloxane copolymers, see, for example, WO2019 / 131973.
[0069] <Carbon Fiber>
[0070] As the carbon fiber, both pitch-based carbon fiber and PAN-based carbon fiber can be used. The carbon fiber can be used alone or in combination of two or more.
[0071] In one embodiment, the content of carbon fiber relative to the entire radio wave absorber is 2 volume % or less. The radio wave absorber of this embodiment can efficiently express radio wave absorption performance with a small amount of carbon fiber compared with the past by making the carbon fiber unevenly present. The content of carbon fiber can be 1.8 volume % or less, or 1.5 volume % or less. In addition, the content of carbon fiber can be 0.5 volume % or more, or 0.8 volume % or more.
[0072] The average length of the carbon fibers is preferably 100 μm to 4000 μm. Within this range, high absorption characteristics can be obtained with a small amount of carbon fibers. The average length of the carbon fibers may be 150 μm or more, or 200 μm or more.
[0073] Here, the average length refers to the average value of the lengths of 25 randomly selected carbon fibers measured using a scanning electron microscope (SEM).
[0074] The average length is the average length of the carbon fibers (raw material) when the radio wave absorber is manufactured. The average length of the carbon fibers in the manufactured radio wave absorber is also preferably within the above range.
[0075] <Optional Ingredients>
[0076] In one embodiment, the radio wave absorber preferably contains hollow particles. Since the density difference between the hollow particles and the carbon fibers is large, the addition of the hollow particles to the resin easily results in uneven distribution of the carbon fibers in the thickness direction.
[0077] Examples of the hollow particles include ceramic balloons, glass balloons, and shiras balloons.
[0078] The average diameter (d50: median diameter) of the hollow particles is preferably 1 / 2 or less of the average length of the carbon fibers. More preferably, it is 1 / 3 or less of the average length of the carbon fibers. The average diameter of the hollow particles is a value based on JIS Z 8819-1:1999.
[0079] The compressive strength of the hollow particles is preferably 8 MPa or more. This is because if the compressive strength of the hollow particles is low, cracks are easily generated when mixed with resin, etc. The compressive strength of the hollow particles is more preferably 10 MPa or more.
[0080] In addition, the compressive strength can be measured by the glycerin method based on ASTM D3102-78.
[0081] The content of the hollow particles relative to the entire radio wave absorber may be 1% by volume or more, or 2% by volume or more, or 10% by volume or less, or 8% by volume or less.
[0082] In one embodiment, the radio wave absorber preferably contains carbon particles, thereby achieving appropriate conduction loss and converting radio waves into heat to obtain absorption capability.
[0083] Examples of the carbon particles include acetylene black, furnace black, channel black, and the like.
[0084] The content of the carbon particles relative to the entire radio wave absorber may be 0.1 volume % or more, or 0.2 volume % or more, or may be 10 volume % or less, or 5 volume % or less, or may be 3 volume % or less.
[0085] The radio wave absorber of this embodiment may contain known resin additives within the scope of being able to solve the problem. As known resin additives, stabilizers for heat, light, ultraviolet rays, etc., lubricants, nucleating agents, plasticizers, antistatic agents, mold release agents, flame retardants, softeners, dispersants, antioxidants, colorants, etc. can be cited.
[0086] The total content of the known resin additives is preferably 50% by mass or less, and more preferably 40% by mass or less in the electromagnetic wave absorber.
[0087] <Manufacturing of Radio Wave Absorber>
[0088] The radio wave absorber of the present embodiment can be manufactured by, for example, mixing the above-mentioned resin, carbon fiber and any components as required and forming them into a sheet. In the mixing, a known dispersing device such as a high-speed disperser, a sand mill, a basket sand mill, a three-roll mill, a ball mill, etc. can also be used as required.
[0089] When mixing, the various components may be mixed at once or separately to obtain a predetermined amount. The order of mixing the various components is not particularly limited.
[0090] As an example of a method for preparing the radio wave absorber of the present embodiment, there can be cited a method of mixing the above-mentioned components into a solution obtained by dissolving a thermosetting resin (liquid substance before curing) or a resin in a solvent, forming the mixed solution into a sheet of desired thickness by film casting, film coating by a coater, etc., and heating. In this method, the uneven existence state of the carbon fiber can be controlled by the standing time of the mixed solution before heating. The standing time and heating time of the mixed solution can be appropriately adjusted in consideration of the viscosity of the resin or resin solution used, the solvent used, etc.
[0091] The concentration of the fixed component in the mixed solution is determined so as to obtain a film thickness appropriate for the frequency at which the maximum absorption capacity of the radio wave absorber can be obtained, and is preferably 80% by mass or less and 5% by mass or more.
[0092] In this embodiment, the thickness of the radio wave absorber ( Figure 1 The T) is preferably 200 to 500 μm. In this embodiment, by making the carbon fibers unevenly present, the radio wave absorption performance can be efficiently exhibited with a smaller amount of carbon fibers than in the past. Therefore, the thickness can be made thinner than in the past. The thickness of the radio wave absorber can be 400 μm or less, or 350 μm or less.
[0093] [Radio wave absorbing structure]
[0094] A radio wave absorption structure according to an embodiment of the disclosed technology includes a stacked structure of the radio wave absorber of the disclosed technology and a radio wave reflector, wherein the radio wave reflector is stacked on a surface of the radio wave absorber on which carbon fibers are unevenly present.
[0095] Figure 2 This is a schematic cross-sectional view of a radio wave absorption structure according to an embodiment of the disclosed technology. The radio wave absorption structure 2 has a structure in which the radio wave absorber 1 is stacked on one surface of a radio wave reflector 21. At this time, a region A side where carbon fibers are unevenly present is formed on the radio wave reflector 21. As a result, the radio wave absorption performance can be improved compared to a case where the same amount of carbon fibers are uniformly dispersed.
[0096] The radio wave reflector is not particularly limited as long as it has the property of not transmitting radio waves but reflecting radio waves, such as metal plates, metal foils, and metal films. It should be noted that a resin layer such as a general adhesive layer may be formed between the radio wave absorber and the radio wave reflector.
[0097] The radio wave absorbing structure can be produced, for example, by forming the radio wave absorber 1 directly on the radio wave reflector 21 or by attaching the radio wave reflector 21 to the radio wave absorber 1 .
[0098] It should be noted that Figure 2 Although a sheet-shaped radio wave absorption structure is exemplified in the embodiment, the radio wave absorption structure of the present embodiment is not limited to a planar body such as a sheet, and can be formed appropriately according to the use site.
[0099] The radio wave absorber and radio wave absorption structure disclosed in the present invention have high radio wave absorption performance in the entire frequency range of 75 GHz to 105 GHz. Specifically, the amount of radio wave absorption in the entire frequency range of 75 GHz to 105 GHz can be made 30% or more.
[0100] In particular, in the frequency range (75 to 80 GHz) of millimeter-wave radar capable of detecting long distances, the amount of radio wave absorption can be made 30% or more, 50% or more, or 60% or more.
[0101] [Composition for radio wave absorber]
[0102] The composition for a radio wave absorber disclosed in the present invention comprises a resin having an organosiloxane structure represented by the following formula (1), carbon fibers, hollow particles, and carbon particles. Furthermore, the content of the carbon fibers in the solid component is 2% by volume or less, the content of the hollow particles in the solid component is 10% by volume or less, and the content of the carbon particles in the solid component is 10% by volume or less.
[0103] [Chemistry 5]
[0104]
[0105] (Where R 1 and R 2 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms).
[0106] The specific components, compounding, suitable examples, etc. in the composition for radio wave absorber of the present embodiment are the same as those of the above-mentioned radio wave absorber. In addition, the composition for radio wave absorber of the present embodiment may contain a known resin additive within a range that can solve the problem.
[0107] The composition for the radio wave absorber of the present embodiment may further contain a solvent. When containing a solvent, the fixed component concentration of the composition is preferably 80% by mass or less, and preferably 5% by mass or more. The solvent is not particularly limited, and for example, N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), cyclopentyl methyl ether (CPME), or a mixed solvent thereof can be used.
[0108] Example
[0109] Hereinafter, the present technology will be described in more detail based on examples, but the present technology is not limited to these examples.
[0110] In the following, operations not specifically described with respect to temperature and pressure conditions were performed at a temperature near room temperature (usually 25° C.) and a pressure at normal pressure (usually 0.1013 MPa).
[0111] Example 1
[0112] Using a rotary mixer (Agito Ri Rentaro ARE-310), 98.9% by volume (after curing) of silicone resin (polydimethylsiloxane: manufactured by Dow Toray Co., Ltd., the main material of Silpot 184 (registered trademark)) and 1.1% by volume of carbon fiber (intermediate fiber (Midfiber), manufactured by Nippon Graphite Fiber Co., Ltd., XN-100-25M, average length 250 μm) were stirred and mixed at 2000 rpm for 2 minutes.
[0113] To the obtained mixed liquid, a curing agent of Silpot 184 (registered trademark) was added in an amount of 1 (volume ratio) relative to the above main material 10, and the mixture was stirred and mixed at 2000 rpm for 2 minutes, and then degassed at 2000 rpm for 2 minutes.
[0114] The degassed mixed solution was poured into a 10 cm square aluminum container and allowed to stand for 50 minutes. The aluminum container was then heated at 100° C. for 40 minutes on a hot plate to cure the mixture, and the cured product (cast film) was peeled off from the aluminum container to prepare a radio wave absorber.
[0115] In Example 1, the mixed solution was left to stand for 50 minutes so that the carbon fibers were unevenly present in the lower portion.
[0116] Example 2
[0117] A radio wave absorbing structure was produced in the same manner as in Example 1 except that the composition of the mixed solution was changed as shown in Table 1 and the solidified product (cast film) was not peeled off from the aluminum container but a laminate of aluminum and the solidified product was prepared.
[0118] Embodiments 3 to 6
[0119] A radio wave absorber was prepared in the same manner as in Example 1 except that the composition of the mixed solution was changed as shown in Table 1. In Examples 3, 5 and 6, a radio wave absorption structure composed of a laminate of aluminum and the cured product was prepared in the same manner as in Example 2 without peeling the cured product from the aluminum container.
[0120] Embodiments 7 to 11
[0121] In a mixed solvent of N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF) and cyclopentyl methyl ether (CPME) (NMP:DMF:CPME=10.3:3.5:1.0 / weight ratio), each component is added at the volume ratio shown in Table 1 and Table 2 (excluding the mixed solvent), mixed and stirred to prepare a mixed liquid.
[0122] The mixed solution was poured into a 10 cm square aluminum container and allowed to stand for 20 minutes. The aluminum container was then heated on a hot plate at 140° C. for 60 minutes to dry the mixed solution, thereby preparing a radio wave absorber as a solidified product (cast film).
[0123] In Examples 7 to 11, the carbon fibers were allowed to be unevenly distributed in the lower portion by leaving the mixed solution to stand for 20 minutes, which was a shorter time than that in Example 1.
[0124] In Example 9, a radio wave absorber was stacked on an aluminum plate serving as a radio wave reflector to produce a radio wave absorbing structure.
[0125] Comparative Example 1
[0126] Each component was added at the volume ratio shown in Table 1, and a mixed solution was prepared in the same manner as in Example 1. The mixed solution was poured into a 10 cm square aluminum container, and heated at 100° C. for 40 minutes on a hot plate without leaving the aluminum container still to cure it, and the cured product (cast film) was peeled off from the aluminum container to prepare a radio wave absorber.
[0127] Comparative Examples 2 to 5
[0128] Except having changed the compounding of the mixed liquid as shown in Table 1, it carried out similarly to Example 1, and produced the radio wave absorber.
[0129] Comparative Example 6
[0130] In a mixed solvent of N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF) and cyclopentyl methyl ether (CPME) (NMP:DMF:CPME=10.3:3.5:1.0 / weight ratio), each component is added at the volume ratio shown in Table 2 (excluding the mixed solvent), mixed and stirred to prepare a mixed liquid.
[0131] The mixed solution was poured into a 10 cm square aluminum container and allowed to stand for 60 minutes. The aluminum container was then heated at 140° C. for 60 minutes on a hot plate to cure the mixture, and the cured product (cast film) was peeled off from the aluminum container to prepare a radio wave absorber.
[0132] The radio wave absorbers and radio wave absorbing structures prepared in the examples and comparative examples were measured for the lower region ( Figure 1 The ratio of carbon fibers contained in area A) 50% and the radio wave absorption characteristics.
[0133] <Method for measuring the ratio of carbon fibers contained in the lower 50% region of the radio wave absorber>
[0134] The radio wave absorber was cut into 8mm×20mm squares to prepare a sample. After measuring the sample with a microfocus X-ray CT device (manufactured by Bruker, SkyScan 2211), a 3D image was reconstructed using image analysis software (manufactured by Ratoc System Engineering, TRI / 3D-VIE), and the carbon fiber was extracted three-dimensionally based on the contrast of the image data caused by the difference in the X-ray absorption coefficients of the resin and the additive (carbon fiber). The fiber length distribution of the extracted carbon fiber was analyzed, and the volume conversion was performed to calculate the volume concentration (vol%).
[0135] <Radio wave absorption characteristics>
[0136] The radio wave absorption characteristics were measured by a free space method.
[0137] Instrument used: PNA microwave network analyzer N5227 (Keysight Technologies)
[0138] Test conditions
[0139] Atmosphere: Atmospheric
[0140] Temperature: Room temperature
[0141] Frequency: 75 GHz to 105 GHz (Table 1)
[0142] Irradiation angle: vertical
[0143] Tables 1 and 2 show the measurement results.
[0144] [Table 1]
[0145]
[0146] [Table 2]
[0147]
[0148] The materials used are as follows.
[0149] (resin)
[0150] PDMS: silicone resin (polydimethylsiloxane: manufactured by Dow Toray Co., Ltd., Silpot 184 (registered trademark))
[0151] Resin A: polycarbonate-polyorganosiloxane copolymer produced in Production Example 2 described later
[0152] Resin B: polycarbonate-polyorganosiloxane copolymer produced in Production Example 3 described later
[0153] (Carbon Fiber)
[0154] ・Intermediate fiber (Midfiber) (manufactured by Nippon Graphite Fiber Co., Ltd.)
[0155] Average length 150μm (XN-100-15M)
[0156] Average length 250μm (XN-100-25M)
[0157] Average length 3000μm (XN-100-03Z)
[0158] (Hollow particles)
[0159] Hollow glass beads (Q-CEL 7040S manufactured by Potters-Ballotini Co., Ltd.)
[0160] (Radio wave reflector)
[0161] Aluminum plate (10cm square, 2mm thickness)
[0162] (other)
[0163] Carbon particles (acetylene black, manufactured by DENKA Corporation, Denka Black (pressure 100%))
[0164] It can be confirmed from Tables 1 and 2 that the embodiment can obtain high absorption characteristics of 30% or more at all frequencies. On the other hand, although Comparative Example 1 has the same components as Example 1, the radio wave absorption amount is less than 30% at all frequencies. It is believed that the main reason is that the proportion of carbon fibers in the lower region of the radio wave absorber is as low as 51% by volume, so the network between the carbon fibers cannot be well formed, and the dielectric constant of the radio wave absorber becomes low.
[0165] Figure 3 The complex dielectric constants (@76 GHz) of the radio wave absorbers prepared in Example 1 and Comparative Example 1 are shown. Thus, it can be confirmed that the complex dielectric constants are greatly different.
[0166] Since Comparative Examples 2, 3 and 5 do not contain carbon fibers, the radio wave absorption at all frequencies is less than 30%.
[0167] In Comparative Example 4, it is considered that the main reason is that the ratio of carbon fibers in the lower region of the radio wave absorber is as low as 52 volume %, so that a network between carbon fibers cannot be well formed, and the dielectric constant of the radio wave absorber decreases.
[0168] In Comparative Example 6, the radio wave absorption characteristics were measured, and the results showed that the radio wave absorption was not more than 30% at all frequencies. The main reason is believed to be that the carbon fibers settled due to the long standing time of the mixed solution, and were too unevenly present on the first surface, so that the radio wave absorber deviated from the appropriate dielectric constant.
[0169] [Manufacturing of Resins A and B (Polycarbonate-Polyorganosiloxane Copolymer)]
[0170] Production Example 1
[0171] (Production of Polycarbonate Oligomer)
[0172] 2000 ppm by mass of sodium dithionite was added to a 5.6% by mass sodium hydroxide aqueous solution relative to bisphenol A (BPA) to be dissolved later. Next, BPA was dissolved in the aqueous solution to a concentration of 13.5% by mass to prepare a sodium hydroxide aqueous solution of BPA.
[0173] The obtained BPA sodium hydroxide aqueous solution was continuously introduced into a tubular reactor having an inner diameter of 6 mm and a tube length of 30 m at a flow rate of 40 L / hr, dichloromethane at a flow rate of 15 L / hr, and phosgene at a flow rate of 4.0 kg / hr. The tubular reactor had a jacket portion, and cooling water was passed through the jacket to maintain the temperature of the reaction solution at 40° C. or less.
[0174] The reaction liquid that had passed through the tubular reactor was continuously introduced into a baffled tank reactor having swept wings and an internal volume of 40 L. In the tank reactor, a sodium hydroxide aqueous solution of BPA was introduced at a flow rate of 2.8 L / hr, a 25 mass % sodium hydroxide aqueous solution was introduced at a flow rate of 0.07 L / hr, water was introduced at a flow rate of 17 L / hr, and a 1 mass % triethylamine aqueous solution was introduced at a flow rate of 0.64 L / hr, and the reaction was carried out.
[0175] The reaction liquid overflowing from the tank reactor was continuously withdrawn and allowed to stand, the aqueous phase was separated and removed, and the dichloromethane phase was collected to obtain a polycarbonate oligomer solution. The concentration of the polycarbonate oligomer was 341 g / L, and the chloroformate group concentration was 0.71 mol / L.
[0176] Production Example 2
[0177] (Manufacture of Resin A)
[0178] 185 mL of the polycarbonate oligomer solution (PCO) prepared in the above-mentioned Preparation Example 1, 445 mL of dichloromethane, 55 g of allylphenol terminal-modified polydimethylsiloxane having an average chain length n of 37, and 0.104 mL (0.75 mmol) of triethylamine (TEA) were placed in a 1 L separable flask having a baffle and a mechanical stirrer with a stirring blade. Under stirring, a sodium hydroxide aqueous solution A (an aqueous solution prepared by dissolving 1.0 g (26.2 mmol) of NaOH in 12 mL of ion exchange water) was added, and polymerization was carried out for 20 minutes.
[0179] To the obtained polymerization liquid, 9.8 g of a dichloromethane solution of p-tert-butylphenol (PTBP: manufactured by DIC Corporation) [a solution prepared by dissolving 1.8 g (12.1 mmol) of PTBP in 6 mL of dichloromethane] and an aqueous sodium hydroxide solution C (a solution prepared by dissolving 9.3 g (32.0 mmol) of bisphenol A, 6.8 g (170.5 mmol) of NaOH and 0.031 g (0.20 mmol) of Na2S2O4 in 100 mL of ion-exchanged water) were added, and the polymerization was carried out for 20 minutes.
[0180] After the polymerization was completed, the polymerization solution was transferred to a separatory funnel and allowed to stand to separate into an organic phase and an aqueous phase. The organic phase was transferred to another separatory funnel and washed with 100 mL of a 0.03 mol / L NaOH aqueous solution and 100 mL of a 0.2 mol / L hydrochloric acid solution in sequence. Then, washing with ion exchange water was repeated until the conductivity of the washed aqueous phase became less than 10 μS / m.
[0181] The washed organic phase was transferred to cotton wool and dried overnight at 48° C. in an explosion-proof dryer (under a nitrogen atmosphere) to form a sheet. The sheet was cut to obtain a PC-POS copolymer (resin A) in a thin sheet form.
[0182] Production Example 3
[0183] (Manufacture of Resin B)
[0184] 185 mL of the polycarbonate oligomer solution (PCO) prepared in the above-mentioned Preparation Example 1, 445 mL of dichloromethane, 77 g of allylphenol terminal-modified polydimethylsiloxane having an average chain length n of 37, and 0.104 mL (0.75 mmol) of triethylamine (TEA) were placed in a 1 L separable flask having a baffle and a mechanical stirrer with a stirring blade. Under stirring, sodium hydroxide aqueous solution A (an aqueous solution prepared by dissolving 2.1 g (52.5 mmol) of NaOH in 24 mL of ion exchange water) was added to polymerize the polycarbonate oligomer and the allylphenol terminal-modified PDMS for 20 minutes.
[0185] To the obtained polymerization liquid, a dichloromethane solution of p-tert-butylphenol (PTBP: manufactured by DIC Corporation) [a solution prepared by dissolving 1.8 g (12.0 mmol) of PTBP in 10 mL of dichloromethane] and an aqueous sodium hydroxide solution C (a solution prepared by dissolving 7.6 g (33.4 mmol) of bisphenol A, 5.8 g (144.3 mmol) of NaOH and 0.015 g (0.1 mmol) of Na2S2O4 in 84 mL of ion exchange water) were added and polymerization was carried out for 20 minutes.
[0186] After the polymerization, the reaction solution was transferred to a separatory funnel and allowed to stand to separate into an organic phase and an aqueous phase. The organic phase was transferred to another separatory funnel and washed with 100 mL of a 0.03 mol / L NaOH aqueous solution and 100 mL of a 0.2 mol / L hydrochloric acid solution. Then, washing with ion exchange water was repeated until the conductivity of the washed aqueous phase became less than 10 μS / m.
[0187] The washed organic layer was transferred to cotton wool and dried overnight at 48° C. in an explosion-proof dryer (under a nitrogen atmosphere) to form a sheet. The sheet was cut to obtain a PC-POS copolymer (resin B) in a thin sheet form.
[0188] Industrial Applicability
[0189] The radio wave absorber disclosed in the present invention can be used as a component for absorbing radio waves in the millimeter wave region in vehicles, civil engineering structures, buildings, port equipment, ship equipment, bridges, power equipment, communication equipment, mechanical equipment, etc. Specifically, it is suitable as a radio wave absorbing shielding component used in millimeter wave radar devices, electrical / electronic instruments, etc. used in ships, airplanes, vehicles, etc. In addition, it is suitable as a useless radio wave absorbing shielding component in a traffic infrastructure environment such as a road guardrail, a tunnel inner wall, or a smart city.
[0190] Although some embodiments and / or examples of the present invention are described in detail above, it is easy for those skilled in the art to apply many changes to these illustrative embodiments and / or examples without substantially departing from the new teachings and effects of the present invention. Therefore, these many changes are included within the scope of the present invention.
[0191] The entire contents of the documents described in this specification and the applications on which the priority claim based on the Paris Convention of the present application is based are cited.
Claims
1. A radio wave absorber comprising a resin and carbon fibers, 60 to 90 volume % of the entire carbon fibers are present in a region from the first surface to half of the total thickness.
2. The radio wave absorber according to claim 1, wherein: The content of the carbon fibers is 2 volume % or less of the total volume.
3. The radio wave absorber according to claim 1 or 2, wherein: Furthermore, hollow particles are contained in an amount of 10 volume % or less of the total volume.
4. The radio wave absorber according to any one of claims 1 to 3, wherein The average length of the carbon fiber is 100 to 4000 μm.
5. The radio wave absorber according to any one of claims 1 to 4, wherein The resin has an organosiloxane structure represented by the following formula (1): In the formula, R 1 and R 2 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms.
6. The radio wave absorber according to any one of claims 1 to 5, wherein Furthermore, carbon particles are contained in an amount of 10 volume % or less of the total volume.
7. The radio wave absorber according to any one of claims 1 to 6, wherein The amount of radio wave absorption in the entire frequency range of 75 GHz to 105 GHz is 30% or more.
8. A radio wave absorbing structure comprising the radio wave absorber according to any one of claims 1 to 7 and a radio wave reflector, wherein the radio wave reflector is laminated on a side of the radio wave absorber on which carbon fibers are unevenly present. The thickness of the radio wave absorber is 200 to 500 μm.
9. The radio wave absorbing structure according to claim 8, wherein: The amount of radio wave absorption in the entire frequency range of 75 GHz to 105 GHz is 30% or more.
10. A composition for a radio wave absorber, comprising a resin having an organosiloxane structure represented by the following formula (1), carbon fibers, hollow particles, and carbon particles, The carbon fiber content in the solid component is less than 2 volume %, The content of the hollow particles in the solid component is less than 10% by volume, The content of the carbon particles in the solid component is less than 10% by volume, In the formula, R 1 and R 2 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms.
Citation Information
Patent Citations
Electromagnetic wave shielding molding
JP2019161208A
Radio wave absorption coating composition, radio wave absorption film, base material with radio wave absorption film and method for producing base material with radio wave absorption film
JP2020111730A
Polycarbonate-polyorganosiloxane copolymer
WO2019131973A1
Electromagnetic wave absorption material and electromagnetic wave absorber
CN108370654A
Electromagnetic wave shielding molded article
CN111279808A
